Implementation of immobilization accessories for positioning of small animals for radiation therapy - Vettorato, M. C. [UNESP]; Girotto, C. H. [UNESP]; Fogaca, J. L. [UNESP]; Vulcano, L. C. [UNESP]; Fernandes, M. A. R. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
Radiation therapy is a modality that is presenting great advances in veterinary medicine worldwide. In Brazil, this therapeutic option is underachieved. The success of this method depends on several factors, including the use of appropriate accessories for protection and immobilization of patients. For the immobilization of small animals during treatment, in addition to sedation and anesthesia, immobilizing accessories, similar to those used in human radiotherapy, are used. This study aimed to present proposals for immobilizing accessories adapted to the positioning of small animals in order to be used in radiotherapy planning. In order to achieve results, accessories were made and tested in a living animal simulating a radiotherapy planning, which proved to be favorable to use in positioning small animals undergoing radiotherapy and for implementation processes.
Keywords: veterinary radiotherapy; immobilizing accessories; small animals